The Evolution of Tertiary Education in Belize and the Impact of COBEC: 1988-2018 - Aird, Cynthia Eve (My University, 2018)
COBEC 1988 is a “bi-national effort recognizing the value of international educational exchange and the benefits of collaborative efforts” which committed its membership to “cooperative development of educational programs and activities in Belize and as well focuses on teacher education as well as on other educational programs.
COBEC Winter Conference February 1, 2018 Wesley Junior College
Keywords: tertiary education; higher education; COBEC